The Influence of the STEM-Based Engineering Design Process Model on High School Students' Creative and Critical Thinking Abilities - Wulan Safitri; Slamet Suyanto; Wanda Agus Prasetya (Postgraduate, University of Mataram, 2024)
STEM-based Engineering Design Process learning model as a learning innovation to improve creative and critical thinking skills. This research aims to determine the influence of the STEM-based Engineering Design Process learning model on creative and critical thinking skills in a multivariate manner, as well as the correlation between students' creative and critical thinking skills on the subject of environmental pollution. The design of this research is Quasi Experimental with a pretest-posttest control group design. The treatment given to the experimental class was learning using the STEM-based Engineering Design Process model, while the control class used the Discovery Learning model with a scientific approach. The results of this research show that there is an influence of the STEM-based Engineering Design Process model on the ability to think creatively and critically in a multivariate manner with a value of sig. in Hotelling's trace from the MANOVA test 0.000 ‹ 0.05, and there is a correlation between creative and critical thinking abilities and the sig value. from the pearson test ‹ 0.000 ‹ 0.05. In conclusion, the STEM-based Engineering Design Process model is able to improve creative and critical thinking abilities, and there is a correlation between creative and critical thinking abilities.